Bond-random model of spin-crossover compounds: similarities and differences from spin glasses - Gudyma, Iurii (Springer Nature Switzerland AG, 2021)
The Ising-like model of spin-crossover solid compounds with random bonds has been studied by the mean-field (infinite range) replica symmetry approximation. An exact solution to the problem is found and analyzed. Interestingly, the temperature stability region at selected intermolecular couplings and standard deviations is quite wide.
Keywords: Research Subject Categories::NATURAL SCIENCES